2022
DOI: 10.1039/d1cy01668g
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum-based double perovskite nanoscale motifs as support media for the methanol oxidation reaction

Abstract: We have correlated the performance of double perovskite metal oxides as support media for the methanol oxidation reaction (MOR) with their intrinsic size, shape, and composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…While most work for MOR or EOR has focused on single perovskites, our group has recently reported that the observed activity is correlated with chemical composition. In fact, we noted that Ni-containing perovskites, such as LaNiO 3 and La 2 NiMnO 6 , were able to achieve comparable activities for MOR and outperformed both LaMnO 3 and the Pt/C standard when these lanthanum-based perovskites were used as supports for Pt nanoparticles . Interestingly, we also observed that anisotropic nanorods achieved a noticeably higher MOR performance as compared with nanocubes possessing a similar size, all else being equal.…”
Section: Introductionmentioning
confidence: 65%
“…While most work for MOR or EOR has focused on single perovskites, our group has recently reported that the observed activity is correlated with chemical composition. In fact, we noted that Ni-containing perovskites, such as LaNiO 3 and La 2 NiMnO 6 , were able to achieve comparable activities for MOR and outperformed both LaMnO 3 and the Pt/C standard when these lanthanum-based perovskites were used as supports for Pt nanoparticles . Interestingly, we also observed that anisotropic nanorods achieved a noticeably higher MOR performance as compared with nanocubes possessing a similar size, all else being equal.…”
Section: Introductionmentioning
confidence: 65%
“…It is widely accepted that the physical properties are strongly influenced by B-site cation disordering, which has a strong correlation with the selection of synthesis routes [ 10 ]. Up to date, various synthetic methods have been developed to synthesize nanostructured LNMO materials, such as but not limited to the solid-state reaction method [ 3 , 10 , 32 , 33 , 34 ], sol-gel process [ 20 , 29 , 35 , 36 , 37 ], gel combustion method [ 38 , 39 ], co-precipitation method [ 40 , 41 ], Pechini method [ 9 , 15 ], molten salt method [ 42 , 43 , 44 ], ionic coordination reaction method [ 45 ], and hydrothermal method [ 46 , 47 ]. Despite the sol-gel process being commonly used in the literature for the synthesis of LNMO NPs, this technique often suffers from being out of control over morphology, and yields poorly-defined NPs.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, highly uniform LNMO NRs with an average diameter of ∼20 nm and length of ~120 nm (aspect ratio = 6.0) were synthesized by using a two-step hydrothermal procedure, where the organic surfactant cetyltrimethylammonium bromide (CTAB) was used as a capping agent [ 46 ]. Very recently, both LNMO nanocubes with sizes in the range of ~70 to 400 nm and LNMO NRs with average diameters of ~50 nm were synthesized by using a surfactant-less hydrothermal method [ 47 ]. It is found that the LNMO NRs have a 1.5-fold increase in the methanol oxidation reaction activity compared to LNMO NPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Direct methanol fuel cells (DMFCs), as a green power generation device that can directly convert chemical energy into electrical energy, play an increasingly important role in daily life. 5,6 In particular, DMFCs have been considered to be a very promising power source in the fields of portable electronic devices, electric vehicles, and aerospace crafts because of their high energy conversion efficiency, wide working temperature range, environmental friendliness, and structural safety. 7,8 As the core component of DMFCs, electrocatalysts effectively enhance the inherently slow kinetics of the anode during the methanol oxidation reaction (MOR), which can contribute directly to the output power density of the fuel cell.…”
Section: Introductionmentioning
confidence: 99%